Уточнена термомеханічна модель вимушених гармонічних коливань фізично нелінійної оболонки з розподіленими трансверсально-ізотропними актуаторами - Карнаухов, В.Г.; Жук, Я.О.; Карнаухова, Т.В. (Видавничий дім "Академперіодика" НАН України, 2007)
Using refined Timoshenko's hypotheses and similar hypotheses for electric field quantities, a thermomechanical model of thin-walled shells with distributed transversely isotropic actuators is presented with taking the dissipative heating and physical nonlinearities into account.